Optimization and utilization of the Taguchi method in the aluminum substrate industry: Effects of dipping duration, temperature, and analytical parameters on surface efficiency - Lazim, Halim Mad; Jusoh, M S; Mashira, H; Ghani, Arif (International Journal of Innovative Research and Scientific Studies, 2025)
This study focuses on improving the electroless nickel (EN) plating process for aluminum substrates in Hard Disk Drive (HDD) production. The process applies a nickel-phosphorus (Ni-P) layer to enhance surface efficiency and reduce defects, which is crucial as the demand for high-capacity HDDs grows. The research examines key factors affecting nickel-phosphorus (Ni-P) deposition, using the Taguchi method, which allows for efficient analysis with fewer experiments. Key parameters studied include nickel and phosphorus content, pH, bath temperature, and dipping time. Results show that low nickel and phosphorus levels, along with a specific pH, significantly enhance surface efficiency. The optimal conditions identified are a bath temperature of 93.5 °C and a dipping duration of 100 minutes. This study underscores the importance of controlling these parameters to improve surface efficiency, which is vital for meeting the growing demand for high-capacity HDDs. The findings can help manufacturers reduce defects, improve yields, and save costs, and the methodology may also be applicable to other plating processes in various industries.